Expression of interferon‐stimulated gene 15‐kDa protein, cyclooxygenase (COX) 1, COX‐2, aldo‐keto reductase family 1, member B1, and prostaglandin E synthase in the spleen during early pregnancy in sheep - Yang, Ling; Liu, Yong; Lv, Wan; Wang, Pengda; Wang, Bin; Xue, Jie; Zhang, Leying (Animal science journal, 2018)
The spleen is a unique lymphoid organ that plays a key role in immune regulation. Interferon‐tau induces upregulation of interferon‐stimulated gene 15‐kDa protein (ISG15) in the uterus during early pregnancy in sheep. Prostaglandins (PGs) have important effects in both the activation and the inhibition of immune response through an autocrine and paracrine manner. In this study, splenic samples were obtained at Day 16 of the estrous cycle, and Days 13, 16, and 25 of pregnancy from ewes, and the expression of ISG15 and PG synthases, including cyclooxygenase 1 (COX‐1), COX‐2, PGE synthase (PTGES), and PGF synthase (aldo‐keto reductase family 1, member B1, AKR1B1), was detected through quantitative real‐time PCR, western blot, and immunohistochemistry analysis. Our results showed that there was upregulation of COX‐2 mRNA and protein at Day 25 of pregnancy, and ISG15 mRNA and conjugated proteins, and AKR1B1 mRNA and dimer at Days 16 and 25 of pregnancy. COX‐2 and AKR1B1 proteins were limited to the capsule, trabeculae, and splenic cords. However, the expression of COX‐1 and PTGES was not affected by early pregnancy. In conclusion, ISG15‐conjugated proteins, COX‐2 and AKR1B1 upregulated in maternal spleen during early pregnancy, which may be beneficial for the placentation in sheep.